Oral events related to low-dose methotrexate in rheumatoid arthritis patients - Carlos Henrique Silva Pedrazas; Mario Newton Leitão de Azevedo; Sandra Regina Torres (Sociedade Brasileira de Pesquisa Odontológica, 2010)
Low-dose methotrexate (MTX) is frequently used for patients with rheumatoid arthritis (RA). High doses of MTX frequently produce side effects. The aim of this study was to explore oral complications of low-dose MTX therapy in a population of RA patients. This is a cross-sectional study in which oral examination was performed on a population of RA patients. Patients undergoing MTX therapy (5-20 mg weekly) for at least six months were included in the study group, and RA patients being treated under another regimen were used as controls. The frequency of oral lesions was compared between groups. The chi-square test was used to compare frequencies. Relative risk (RR) and its confidence interval (CI) were established. Significance level was set at 0.05. Twenty-eight RA patients on a low-dose MTX regimen and 21 controls were enrolled in the study. Oral lesions were found in 22 patients (78.6%) undergoing MTX therapy, and in 5 patients (23.8%) undergoing other therapies (p < 0.001). There were no significant differences regarding age, gender or dosage. The most common oral events observed in patients in the MTX group were ulcerative/erosive lesions (60.7%) and candidiasis (10.7%). Patients in the control group presented lower prevalence of the same lesions (p < 0.001). The RR for developing oral lesions was 11.73 (CI 2.57 - 58.98), with low-dose MTX therapy. In conclusion, the prevalence of oral mucosa lesions in RA patients receiving low doses of MTX therapy is higher than in RA patients not receiving the drug.